A influência da dança nos corpos das crianças pequenas e na construção de suas identidades - Floriano, Vitória de Lima (Universidade Federal de São Carlos, 2021)
This work presents the result of a bibliographical research, which sought to understand if the contact with dance and expressive movement influences the bodies of young children and how this happens. Seeking to answer the problem-question “How does dance influence the bodies of young children and the construction of their identities?”, the work is constituted as follows: Chapter I brings a memorial that reports a little about the author's trajectory regarding to object of research, contextualizing its connection to the theme. Chapter II addresses the concepts of dance, children and childhood that sustain the work, considering dance as an expression in the process of discovery and development of children's cultural identity, as well as reflecting on the insertion of dance in formal education. The results of the investigation reveal that dance influences the development of children's cultural identity in order to enable the discovery of the body, self-knowledge and is capable of giving new meaning to the experiences that children live with their bodies. It was verified that dance enables children to establish relationships between their bodies and the world around them, drawing connections between people and society, forming their identity from their bodies, placing themselves in the community in a critical way.
The influence of dance on young children's bodies and on the construction of their identities
Keywords: Dança; Dance; Crianças; Children; Corpo; Body; Identidade; Identity; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO